2017
DOI: 10.1002/lary.26873
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory function before and after multimodal treatment in chronic rhinosinusitis patients

Abstract: 4. Laryngoscope, 128:E86-E90, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 43 publications
(64 reference statements)
2
40
2
Order By: Relevance
“…After close evaluation of the publications, 24 studies reached the inclusion criteria for this review. These have been published over the last 20 years and used the USPIT or single components or the whole battery of the Sniffin’ Sticks test . Almost all the included studies were published in the period from 2007 to 2018; only one earlier study from 1994 was identified …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After close evaluation of the publications, 24 studies reached the inclusion criteria for this review. These have been published over the last 20 years and used the USPIT or single components or the whole battery of the Sniffin’ Sticks test . Almost all the included studies were published in the period from 2007 to 2018; only one earlier study from 1994 was identified …”
Section: Resultsmentioning
confidence: 99%
“…Six studies used the 40‐item UPSIT . Two studies used a combination of at least two (sub‐) tests (I and T), and seven trials used the whole TDI‐score of the Sniffin' Sticks Set …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired olfaction is one of the cardinal symptoms of CRS and can be found in 30% to 78.2% of patients, varying somewhat by age, gender, and presence of polyps . Medications, primarily in the form of oral or topical corticosteroids, have been shown to provide demonstrable improvement in olfaction . Similarly, numerous studies have confirmed significant improvement in olfactory function after sinus surgery .…”
mentioning
confidence: 99%